تقرير المخدِّرات العالمي 2015 - United Nations Office on Drugs; Crime (United Nations, 2015)
The World Drug Report provides an annual overview of recent developments for various drug categories. Chapter one of the World Drug Report 2015 provides a global overview of the latest developments with respect to opiates, cocaine, cannabis and synthetic drugs, ranging from production to trafficking as well as consumption and the health impact of drug use. Chapter two focuses on Alternative Development, its relation to illicit cultivation, and also within the broader context of the development agenda.